2022
DOI: 10.3390/ijerph192013300
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality and Exercise Training Enhance Brain, Cognitive, and Physical Health in Older Adults with Mild Cognitive Impairment

Abstract: We investigated the effectiveness of virtual-reality-based cognitive training (VRCT) and exercise on the brain, cognitive, physical and activity of older adults with mild cognitive impairment (MCI). Methods: This study included 99 participants (70.8 ± 5.4) with MCI in the VRCT, exercise, and control groups. The VRCT consisted of a series of games targeting different brain functions such as executive function, memory, and attention. Twenty-four sessions of VRCT (three days/week) were performed, and each session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…In this regard, it has been reported that in older adults with mild cognitive impairment, aerobic and resistance training interventions for 24 weeks significantly reduced theta/beta ratio, which reflects improvements in attention-related functions, in the temporal and parietal lobes, and in the delta/alpha ratio, which is associated with cognitive impairment, in the frontal, temporal, and parietal areas [58]. Furthermore, Dimitrova et al [59] emphasized that just 20 min of moderate exercise increases the EEG amplitude from 320 to 700 ms at the Cz site and enhances executive task performance in older adults.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, it has been reported that in older adults with mild cognitive impairment, aerobic and resistance training interventions for 24 weeks significantly reduced theta/beta ratio, which reflects improvements in attention-related functions, in the temporal and parietal lobes, and in the delta/alpha ratio, which is associated with cognitive impairment, in the frontal, temporal, and parietal areas [58]. Furthermore, Dimitrova et al [59] emphasized that just 20 min of moderate exercise increases the EEG amplitude from 320 to 700 ms at the Cz site and enhances executive task performance in older adults.…”
Section: Discussionmentioning
confidence: 97%
“…It is difficult to determine the cause of the difference in brain activity observed in the two ADHD subgroups. An increased theta/beta ratio has been observed in conditions such as cognitive impairment in elder people [ 52 , 53 ], and in Lewy body disease [ 54 ]. Furthermore, a study on P300 and the theta/beta ratio suggests that it could be used as a marker of cognitive processing capacity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“… Park, 2022 [ 39 ] Korea Older adults with MCI Joystick, computer 56 (23/33) CG = 72.04 ± 2.42 EG = 71.93 ± 3.11 VR-based training programs (a VR-based spatial cognitive task crafted to enhance spatial memory (32 sessions)). A VR-based spatial cognitive task crafted to enhance spatial memory (24 sessions) 56 sessions, 45 min a session, 3 days a week for 8 weeks Zheng, 2022 [ 47 ] China Older people with dementia A Kinect sensor and a console 38 (9/29) CG = 84.26 ± 5.48 EG = 81.74 ± 5.79 Game (using the Kinect game Fruit Ninja as an exercise intervention to enhance hand-eye coordination and motor skills) Receiving usual therapy, including One h/day, 5 days/week for 8 weeks Yang, 2022 [ 40 ] Korea Older adults with MCI An Oculus VR headset (Oculus quest headset) and two wireless hand controllers 66 (9/57) CG = 72.7 ± 5.6 EG = 72.6 ± 5.4 Game (Four games encompassing various brain domains, such as attention and working memory) Educational seminars focusing on health-related subjects, including advice on nutrition and exercise for preventing geriatric diseases. A total of 24 sessions (each VR training session lasted for 100 min) for eight weeks.…”
Section: Methodsmentioning
confidence: 99%